2018
DOI: 10.4103/0366-6999.240798
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Nerve Stimulation in Amyotrophic Lateral Sclerosis

Abstract: Background:Nowadays, it is widely known that decremental responses in low-frequency repetitive nerve stimulation (LF-RNS) are frequently observed in patients with amyotrophic lateral sclerosis (ALS). The pathological mechanism of this phenomenon remains unknown. This study aimed to illuminate the features of RNS in Chinese patients with ALS.Methods:Clinical and electrophysiological data of 146 probable and definite ALS patients who underwent RNS were retrospectively enrolled and analyzed. LF-RNS (3 Hz) was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 35 publications
6
20
0
Order By: Relevance
“…Moreover, this study showed that the onset of ALS did not affect the RNS decrement responses, which was consistent with previous research (8,18). However, some studies have shown that patients with upper limb onset had higher decremental percentages compared with those with other sites of onset (7,17). The underlying reason for these differences is unclear.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, this study showed that the onset of ALS did not affect the RNS decrement responses, which was consistent with previous research (8,18). However, some studies have shown that patients with upper limb onset had higher decremental percentages compared with those with other sites of onset (7,17). The underlying reason for these differences is unclear.…”
Section: Discussionsupporting
confidence: 91%
“…The patients in the positive decrement group had lower ALSFRS-R scores compared with those in the decremental negative group, suggesting that the former were worse. Some studies have shown that the disease progressed more rapidly in ALS patients with a positive decrement (4,8,13,14), but others contradicted this (5,7,(15)(16)(17). If the RNS decrement responses were not related to the disease progression, the interpretation of the mechanism of decrement responses, the early neural reinnervation, may need to be corrected (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That's why we think multicenter retrospective studies are needed in the future. Secondly, present statistic analysis shows the positivity rate of 3Hz RNS test delivered to the accessory nerve in upper-limb-onset group is 60.6%, leading all the others and followed by bulbar group (45.0%) and lower limb group (32.9%), which is in line with some previous study (Sun et al, 2018;Hatanaka et al, 2017;Hu et al, 2018;Miyaji et al, 2018;Clark et al, 2016). The probable reason for this obviously high positivity rate in the upper-limb-onset group may be ALS's preference for spreading around its onset site.…”
Section: 5supporting
confidence: 91%